Anđelija Lazarević as an Artist: The Representation of Women in Painting during the First Half of 20th Century (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This article explores three connected topics: the representation of women in fine arts and, more precisely, specific spaces which they occupied on canvases at the beginning of the 20th century; the status of the first generation of women painters that came out of the art school led by Rista and Beta Vukanović; and the personal and intellectual biography of the painter Anđelija Lazarević, her education and artistic opus. The article identifies paintings whose titles and compositions in particular provide us with more knowledge about women’s position in society in those times, and indicate that the patriarchal ideology from that epoch generated certain patterns in the visual representations. The examples of concrete art criticism are used to enable better understanding of the unequal position of women painters and men painters. Painter and writer Anđelija Lazarević lived and worked in such a social environment. Unfortunately, her legacy consists of only few artifacts, paintings and aquarelles.
Keywords: Anđelija Lazarević; Beta Vukanović; painting; women spaces